Reinterpretation of the Aggañña Sutta for Addressing Contemporary Social Challenges of Caste and Class - K.C., Jit Bahadur (Prajñā Journal of Buddhist Studies, 2026)
The Aggañña Sutta, one of the highly significant discourses of the Pāli Buddhist tradition, provides a robust criticism of caste and class hierarchies and further envisions a society based on ethical values and equality. In this study, it is attempted to find a modernist reading of the Aggañña Sutta in order to comprehend a reformation of the present day’s social practices regarding building just and moral societies. These include an analysis of the text's historical context, how it destabilizes Brahmanical authority, and the cosmogonical myth explaining the beginnings of society, which the research reveals can present social hierarchies as constructed rather than inevitable. Given this, the paper demonstrates how the concepts learned from the Aggañña Sutta are useful for minimizing the class and cast systems still prevailing in contemporary society, encouraging ethical leadership, and achieving interreligious harmony. The interconnectedness of the text to contemporary causes further includes Dalit Buddhism as well as other groups and organizations of social justice. Recognizing the possible challenges of applying the contextual proverbs mentioned in the Aggañña Sutta to present-day contexts, the article also emphasizes the significance of the given text for envisioning a fair and inclusive society. The Sutta and its proverbs stand as enduring guidelines for addressing inequality and appear as an eternal tool for overcoming injustice and creating a harmonious society.